Pemanfaatan Gamifikasi dalam Ekopedagogi untuk Meningkatkan Keterampilan Membaca dan Menulis Anak - Nanda Septiana; Mutik Nur Fadhilah (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
Ecopedagogy offers an approach to the importance of sustainable education, to raise critical awareness of environmental impacts. Through the integration of game elements, such as challenges, points, and rewards, in learning that focuses on environmental themes, this study aims to increase students' motivation and engagement in the learning process related to children's reading and writing. This research method uses a literature study, which involves analyzing relevant literature, including scientific articles, books, and recent research reports. This method allows for the exploration of information on how gamification can be applied to improve literacy skills, as well as how social interaction in game-based activities can strengthen students' understanding of learning materials. The results showed that students who participated in gamification activities experienced significant improvements in reading and writing skills, and were more motivated and engaged in learning. Collaboration between students can strengthen their sense of responsibility for the environment, and improve critical thinking skills. These findings suggest that the integration of gamification in ecopedagogy can create a more holistic and effective learning experience, contributing to the development of literacy as well as environmental awareness. This article provides recommendations for educators to integrate gamification into the curriculum as a tool to create more interactive, engaging, and relevant learning in the modern era.